School Engagement in Relation to Body Mass Index and School Achievement in a High-School Age Sample - Kristin E. Finn; Myles S. Faith; Young S. Seo (Hindawi Limited, 2018)
Purpose. Research has documented an inverse relationship between body mass index (BMI) and school achievement but has failed to empirically explain it. We tested whether this association among adolescents can be explained in part by student engagement. Methods. A self-report survey about health and school behaviors was completed by 196 high school students; BMI and achievement data were obtained from school records. Three forms of engagement were assessed: behavioral, presenteeism, and affective. Associations of engagement with BMI and achievement were examined, and mediation analyses were conducted. Results. The simple relationship between BMI and achievement was confirmed and demonstrated that BMI was negatively related to academic achievement. Higher BMI was also significantly correlated with lower classroom participation. Mediation tests showed the significant relationship between BMI and achievement was reduced after accounting for behavioral engagement but not affective engagement. Conclusions. These novel findings shed light on why heavier students often experience lower academic achievement. Intervention studies targeting barriers to classroom engagement among overweight and obese youth are needed so that their academic potential is not compromised.